Effects of Ocimum Sanctum (Tulsi) on Blood Glucose level of Alloxan induced Hyperglycemic Rats (KYAMC Journal, 2017)
Blood Glucose lowering properties of Ocimum Sanctum (OS), a renowned medicinal species, were assessed by measuring the levels of blood glucose in the plasma of the hyperglycemic Long Evans rats. The feeding of 1% powder of OS with normal diet for 21 days to hyperglycemic rats significantly reduced serum blood glucose level (p < 0.01). The present study suggests that the blood glucose lowering effects of OS probably serve as a new potential natural product for the treatment of hyperglycemia.KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 386-390